Unleashing the Potential of Microbial Natural Products in Drug Discovery: Focusing on Streptomyces as Antimicrobials Goldmine - Bansal, Himangini; Singla, Rajeev K.; Behzad, Sahar; Chopra, Hitesh; Grewal, Ajmer S.; Shen, Bairong (Current Topics in Medicinal Chemistry, 2021)
The natural product specialized metabolites produced by microbes and plants are the backbone of our current drugs. Ironically, we are in a golden age of understanding natural product biosynthesis, biochemistry, and engineering. These advances have the potential to usher in a new era of natural product exploration and development, taking full advantage of the unique and favorable properties of natural product compounds in drug discovery. There is now an increasing realization that these privileged structures represent the optimal starting point for the development of clinically viable assets. Here, we outline the current state-of-the-art in antimicrobial natural product drug discovery, specifically Streptomyces species, with a specific focus on how the emerging field of synthetic biology is delivering the tools and technologies required to unlock the therapeutic potential of natural products. We illustrate how these approaches are circumventing many of the problems that have historically plagued conventional screening programs, enabling the expedient discovery of new molecules with novel functions.
Keywords: Metabolites